Enhancing capacitance behaviour of CoOOH nanostructures using transition metal dopants by ambient oxidation - Zhang, Hongzhou; Schmitt, Wolfgang; Maguire, Pierce (My University, 2016)
Cobalt hydrate and doped binary Co0.9M0.1OOH (M = Ni, Mn, Fe) nanorings of 100-300 nm were fabricated in solution through a facile ambient oxidation method. A transformation from Co0.9Ni0.1(OH)2 nanodiscs to hollow Co0.9Ni0.1OOH nanorings was observed with prolonged reaction time. Core-shell nanodiscs have elemental segregation with a Co(OH)2 core and Ni(OH)2 shell. Co0.9Ni0.1OOH nanorings displayed a higher electrochemical capacitance than Mn and Fe doped nanorings materials or materials with disc-like geometries.
PUBLISHED
Keywords: geometries; geometries